2007
DOI: 10.1002/ana.21117
|View full text |Cite
|
Sign up to set email alerts
|

Environmental risk factors for multiple sclerosis. Part I: The role of infection

Abstract: Although genetic susceptibility explains the clustering of multiple sclerosis (MS) cases within families and the sharp decline in risk with increasing genetic distance, it cannot fully explain the geographic variations in MS frequency and the changes in risk that occur with migration. Epidemiological data provide some support for the "hygiene hypothesis," but with the additional proviso for a key role of Epstein-Barr virus (EBV) in determining MS risk. We show that whereas EBV stands out as the only infectious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
776
1
25

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 948 publications
(824 citation statements)
references
References 139 publications
(176 reference statements)
22
776
1
25
Order By: Relevance
“…Another explanation is the "hygiene hypothesis" [80] , which states that the high rates of infection in third world countries explain the relatively low incidence of MS near the equator in comparison with near the 2 poles [80] . This is further supported by the experimental data from animal studies, which show that helminth infections protect from experimental autoimmune diseases, including EAE [81] .…”
Section: Vitamin D and Msmentioning
confidence: 58%
“…Another explanation is the "hygiene hypothesis" [80] , which states that the high rates of infection in third world countries explain the relatively low incidence of MS near the equator in comparison with near the 2 poles [80] . This is further supported by the experimental data from animal studies, which show that helminth infections protect from experimental autoimmune diseases, including EAE [81] .…”
Section: Vitamin D and Msmentioning
confidence: 58%
“…Both genetic [1] and environmental [2] factors are thought to be involved in MS. Among the latter, the g-herpesvirus EBV has been repeatedly associated with this disease [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Both genetic [1] and environmental [2] factors are thought to be involved in MS. Among the latter, the g-herpesvirus EBV has been repeatedly associated with this disease [2][3][4]. Large seroepidemiological studies [5][6][7][8] and cellular immune response assessments [9][10][11][12] have demonstrated enhanced EBV-specific immune responses in the blood of MS patients.…”
Section: Introductionmentioning
confidence: 99%
“…It is accompanied by a wide continuum of signs and symptoms with a profound effect on the communication between nerve cells inside the brain and spinal cord [1]. Although there is incomplete understanding of the basic mechanisms behind MS pathogenesis, evidence suggests heterogeneous etiologies of MS, implying the role of multiple environmental factors in its course and development [3][4][5].…”
Section: Introductionmentioning
confidence: 99%